The validity and reliability of Pictorial Pediatric Symptom Checklist in children of 4-5 ages - KARACA, SEMRA (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2019)
Objective: The objective of this study is to carry out the validity and reliability of Pictorial Pediatric Symptom Checklist (PPSC), in preschool children of 4-5 ages. Methods: This methodological study was carried out by permission of ethics committee from Marmara University Institute of Health Sciences Ethics Committee and permission of Duzce Provincial National Education Directorate. The population of the study consists of 1.512 parents with children of 4-5 ages studying in 26 preschool education institutions in Duzce. The sample of the study is composed of 759 parents who accept to participate in the study and meet the admission criteria. MINRES Factor Analysis and Confirmatory Factor Analysis (CFA) were used to identify and support of the validity of PPSC. The Cronbach's alpha internal consistency, test-retest and Spearman-Brown reliability coefficients were calculated in order to assess the reliability of the checklist. Findings: It was observed that the dataset of the checklist meet multivariate normal distribution and multicollinearity assumptions. According to Cronbach's alpha internal consistency and test-retest validity coefficients, the overall reliability of the checklist is at an acceptable level. As a result of factor analysis, the construct validity of PPSC with five-factor structure was investigated with CFA. Although the suggested model was not considered as meaningful (chi(2)=460.02, df=365, p=0.001), the model has a good fit because it is RMSEA<0.05 and chi(2)/df<2, when other model fit indexes were analyzed. The model has an acceptable fit as indexes SRMR<0.07, CFI, NFI, GFI, and AGFI are close to the values 0.90 or 0.95. Conclusion: The findings show that the PPSC is a valid and reliable screening tool offering the opportunity of identifying psychosocial and behavioral problems in preschool children.
Keywords: Pictorial Pediatric Symptom Checklist; validity; reliability; preschool children; LOW-INCOME; HEALTH; CARE